Means to Enhance the Production of Water from Solar Thermal Pasteurization System - Bajracharya, Tri Ratna; Kunwar, Anil (Journal of the Institute of Engineering, 2011)
A density driven solar thermal pasteurization system has been installed for the purpose of purification of water. The main components of this system are evacuated tube collectors with heat pipe, convection tube, holding tube, insulation system, heat exchanger and supply tank. The daily volume of water produced from the system as the pasteurized output reached its maximum value of 4 litres as measured in the days of first two weeks of February, 2011. The main parameters affecting the production rate of water considered are amount of solar insolation falling on the collector area during the peak 3 sunshine hours, mean temperature of water in the heat exchanger and the diameter of the pipe used in the convection tube. It has been known that the daily production volume of water increases with the higher values of solar insolation and the mean temperature of the heat exchanger whereas diameter of the tube used in the convection loop should be smaller to produce more water at the output. Keywords : Solar; Pasteurization system; purification DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5095 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 39-47 Uploaded Date: 19 July, 2011